Reprogramming tendon healing: a guide to novel molecular tools - Peniche Silva, Carlos Julio; Balmayor, Elizabeth R.; van Griensven, Martijn (Frontiers in Bioengineering and Biotechnology, 2024)
Tendons are a frequent site of injury, which greatly impairs the movement and locomotion of patients. Regrettably, injuries at the tendon frequently require surgical intervention, which leads to a long path to recovery. Moreover, the healing of tendons often involves the formation of scar tissue at the site of injury with poor mechanical properties and prone to re-injury. Tissue engineering carries the promise of better and more effective solutions to the improper healing of tendons. Lately, the field of regenerative medicine has seen a significant increase in the focus on the potential use of noncoding RNAs (e.g. siRNAs, miRNAs, and lncRNAs) as molecular tools for tendon tissue engineering. This class of molecules is being investigated due to their ability to act as epigenetic regulators of gene expression and protein production. Thus, providing a molecular instrument to finetune, reprogram, and modulate the processes of tendon differentiation, healing, and regeneration. This review focuses particularly on the latest advances involving the use of siRNAs, miRNAs, and lncRNAs in tendon tissue engineering applications.